Assessment of Knowledge and Attitude regarding Hepatitis B infection and its prevention among medical undergraduate students of a medical college of Western Uttar Pradesh - Negi, Rudresh; Agarwal, Renu; Virmani, Ishaan (Indian Journal of Community Health, 2025)
Background: Compared to the general population, healthcare workers (including medical students) have a greater chance of developing a hepatitis B infection. There has often been a lack of awareness and observance of precautionary measures among the students. Aim & Objectives: To assess knowledge, attitude & awareness of hepatitis B infection and preventive strategies among medical students. Methodology: This cross sectional study was conducted for 6 months, enrolled all medical undergraduate students from all the batches studying at a medical college in Agra. A questionnaire-based proforma was filled out by each participant. Results: Mean age (SD) of participants was 22 ± 0.92 years with 53% female participants. Mean knowledge score among the participants was 10.6 ±2.19 and mean attitude score was 26.4±2.24. Knowledge score was significantly associated with age, sex, professional year (p value 0.000), religion (p value 0.021). Attitude was significantly associated with age (p value 0.048), sex, permanent residence (p value 0.002), socioeconomic class, knowledge (p value 0.000). Conclusion: There is need to improve knowledge regarding hepatitis infection from the very beginning itself to ensure proper attitude and hopefully better preventive practices among the students those will become future doctors in coming time.